motivasi kader kesehatan untuk melakukan penyuluhan dalam pelaksanaan sistem 5 meja di desa Bangun kecamatan Pungging kabupaten Mojokerto - Frilasari, Heni; Ika sari, Arista (JURNAL KEPERAWATAN BINA SEHAT, 2011)
The presence of cadres in posyandu as a one of delivery system needs service for basic health. This is because the cadre as a figure nearest to the community. Posyandu can be run well when the cadres are active to implementing integrated health activities in the implementation of the system 5 tables. But not all posyandu wanna do the concept of five tables with a variety of reasons, ranging from infrastructure to human resource constraints, particularly for the implementation of the extension table. The purpose of this study to know the motivation of health’s cadres to carry out extension in the implementation of the five tables system at the Bangun village subdistricts Pungging Mojokerto. Design used in this research is descriptive, population are taken all of health cadres at the Bangun village District Pungging Mojokerto many as 15 people by using sampling jenuh techniques. The variables in this research is motivation of health cadres to do extension in the implementation of 5 tables system. The instrument used in this study is questionnaire and categorized then tabulated and categorited. The results of the questionnaire analysis using frequency distribution tables from the study showed that nearly half of respondents have low motivation as many as seven people (46.7%). It can be caused by education , the average respondent education is basic education, respondents also worked as a farmer, and a less supportive environment can also reduce the motivation of respondents.Key Word: Motivation, Health’s Cadres, 5 Tables System, Extension